Elevated levels of serum amyloid A indicate poor prognosis in patients with esophageal squamous cell carcinoma - Wang, Jun-Ye (BioMed Central, 2012)
BACKGROUND: Increase of Serum amyloid A (SAA) level has been observed in patients with a variety of cancers. The objective of this study was to determined whether SAA level could be used as a prognostic parameter in patients with esophageal squamous cell carcinoma (ESCC). METHODS: SAA levels were measured by rate nephelometry immunoassay in 167 healthy controls and 167 ESCC patients prior to surgical resection. Statistical associations between clinicopathological observations and SAA levels were determined using the Mann–Whitney U test. The clinical value of SAA level as a prognostic parameter was evaluated using the Cox’s proportional hazards model. RESULTS: SAA levels were significantly higher in patients with ESCC compared to levels in healthy controls (13.88 ± 15.19 mg/L vs. 2.26 ± 1.66 mg/L, P < 0.001). Elevation of SAA levels (≥ 8.0 mg/L) was observed in 54.5% (91/167) of patients with ESCC but not in healthy controls. SAA levels were associated with tumor size (P < 0.001), histological differentiation (P = 0.015), T classification (P < 0.001), clinical stage (P < 0.001), lymph node metastasis (P < 0.001) and distant metastasis (P < 0.001), but not with the age and gender of the patients or tumor location. Multivariate analysis revealed that patients with an elevated level of SAA (≥ 8.0 mg/L) had significantly lower 5-year survival rate than those with non-elevated SAA (< 8.0 mg/L, log-rank P < 0.0001). CONCLUSIONS: An elevated level of preoperative SAA was found to associate with tumor progression and poor survival in patients with ESCC.